Growth and characterization of AlGaN/GaN HEMT heterostructures on 100-mm Si (111) by MBE - Manvi Agrawal (2013)
III-nitride semiconductors have received significant research attention and undergone immense development due to their widely found applications in microelectronic and optoelectronic devices. Among them, GaN based materials promise great potential for high frequency, high power, and high temperature applications because of their excellent material properties such as wide band-gap, high break down field, high saturation velocity, and high electron mobility, mechanical and thermal stability. However, due to the unavailability of native substrates, GaN based materials are grown heteroepitaxially on foreign substrates such as SiC, sapphire and Si. Of these potential substrates, Si is a more preferred option on account of favorable factors such as low cost, large size and easy availability. Besides, Si is an excellent choice for microelectronics integration of GaN with its matured technology. However, the large lattice mismatch of ~ 17% and the thermal expansion coefficient (TEC) mismatch of ~ 54% are the major challenges in GaN growth on this substrate. In fact, thick GaN layers are needed to yield a device quality layer, which is particularly challenging to achieve on large diameter Si substrates due to high wafer bowing and cracking of the layers. This dissertation focuses on the growth optimization and characterization of AlGaN/GaN heterostructures on 100-mm Si (111) substrates for high electron mobility transistor (HEMT) applications using plasma assisted molecular beam epitaxy (PA-MBE) and ammonia MBE techniques. In order to achieve AlGaN/GaN HEMTs on Si with good two-dimensional electron gas (2DEG) properties, the III/V ratio has been optimized to obtain smooth surface morphology, good crystalline quality and strain-free AlN and GaN layers in the intermediate growth regime by PA-MBE. The effect of III/V ratio on the polarity of AlN and GaN layers in the metal-rich growth regime has also been studied. Al metal flux is found to play a major role in controlling the polarity of AlN layers and hence, determining the polarity of the subsequent GaN layers, which in turn is essential for the development of the conventional Ga polar AlGaN/GaN HEMTs grown on Si (111). Due to the narrow growth window of PA-MBE, a bilayer based technique using in-situ reflection high energy electron diffraction (RHEED) is employed in order to obtain reproducible material properties of the GaN layers. A smooth surface morphology having a root mean square (RMS) roughness of ~ 1.0 nm is obtained for 5×5 μm2 scan area. The screw dislocation density obtained is 4×109 cm-2 while the edge dislocation density ranges from 1.5 to 2.0×1011 cm-2. In addition, nearly relaxed and crack-free GaN layers with thicknesses up to 1.5 μm are obtained with a small residual tensile strain of 0.02%. Further, AlGaN/GaN HEMT heterostructures have been optimized to obtain the highest 2DEG mobility and sheet carrier density of 1100 cm2/V.s and 9×1012 cm-2, respectively. As mentioned above, the growth by PA-MBE technique provides narrow growth window making the precise control of III/V ratio difficult. Moreover, low cracking efficiency of the nitrogen molecule limits the growth rates to be low in the range of 0.1 to 0.4 μm/hr. This dissertation also discusses the growth of AlGaN/GaN HEMT heterostructures by ammonia MBE, as it offers several advantages such as wider growth window, better uniformity, stable growth conditions and easy cracking of the ammonia molecule to produce active nitrogen for higher growth rates. Another advantage is the fact that metal-polar layers are always obtained in the ammonia rich growth conditions and hence are better suited for the growth of conventional Ga polar AlGaN/GaN HEMT heterostructures. Unlike PA-MBE, the use of stress mitigating layers is necessary for the growth of thick GaN layers on Si by ammonia MBE. To address this, an in-depth study has been done on the growth of GaN layers using AlGaN/AlN and AlN/GaN as stress mitigating layers on Si (111). The structural properties of GaN grown on AlGaN/AlN stress mitigating layers are assessed as a function of AlN thickness and AlGaN growth temperature. GaN grown on thicker AlN shows reduced dislocation density and lesser tensile strain. Three-dimensional (3D) growth regime is observed for GaN grown at lower AlGaN growth temperature while higher AlGaN growth temperature results in two-dimensional (2D) growth mode. The origin of tensile strain in the GaN layers is also determined by comparing the experimentally and theoretically obtained strain values. The average plastic relaxation due to the dislocation looping and the tensile strain generated due to the grain coalescence are found to be the major factors influencing the strain states of GaN grown on AlGaN/AlN stress mitigating layers. The growth of GaN layers using AlGaN/AlN stress mitigating layers is found to have resulted in either 3D surface morphology or high threading dislocation density, both of which are detrimental for the 2DEG properties in AlGaN/GaN HEMT heterostructures. On the other hand, GaN grown using AlN/GaN as stress mitigating layers exhibit 2D growth mode and reduced threading dislocation density. The bending and looping of dislocations at the two subsequent AlN/GaN interfaces have been found to be the reason for the annihilation of the dislocations. In addition, high lattice mismatch induced compressive strain at the second AlN/GaN interface and the slow relaxation process of the subsequently grown thick GaN layers are found to be effective in obtaining crack-free GaN. GaN layers are further improved by increasing the growth rate resulting in smoother surface morphology and compressively strained GaN layers. Crack-free buffer layers with thicknesses up to 1.7 μm were obtained with screw and edge dislocation density of 1.6×109 and 4.6×1010 cm-2, respectively. Subsequently, AlGaN/GaN HEMT heterostructures using AlN/GaN stress mitigating layers have been optimized to exhibit the highest 2DEG mobility and sheet carrier density values of 1350 cm2/V.s and 1.2×1013 cm-2, respectively.